Fake News Detection Using Machine Learning - Mohammed Amin, Pshko (AI Society & STMIK Indonesia, 2023)
Today one of the fattest environments for opinion exchanging is the internet. Individuals can share their data or post any news they want through social media platforms. these data sharing platforms do not verify the users or the data and information they post. so, some users can share fake or untrusted data through these platforms on the Internet. Fake news is described as a propaganda tool against any Individual, society, government, or political party. Humans cannot detect and understand all the fake news or data through these online platforms. In this study, the challenge has been defined through a Machine learning concept. machine learning classification was applied to the dataset. Finally, a comparison of the working of these classifiers is presented along with the results, Decision Tree and Support Vector Machine classification models are performing well.